(untitled) (Research, Society and Development, 2024)
Complementary Medicine has gained recognition in Brazil, with the Ministry of Health promoting alternative practices as new health approaches. These practices provide alternatives to social medicalization, viewing health as a complete state of physical, mental, and social well-being, rather than merely the absence of disease. The goal of Integrative and Complementary Practices (ICPs) is to promote self-care and holistic health awareness. This article explores the application of ICPs in the health promotion of cancer patients through a systematic literature review, analyzing four main stages: identification, selection, eligibility, and inclusion. Data collection occurred between April and May 2021 in the PubMed, Virtual Health Library (BVS), and Web of Science databases, utilizing descriptors such as “Pain,” “Neoplasms,” and “Complementary Therapies.” Results highlight the necessity of a humanistic approach by nurses, who must consider the personal context of cancer patients, focusing not only on biological interventions but also on existential aspects. The role of the nurse is crucial in patient recovery, valuing their emotions and contributing to self-esteem. Although ICPs are still emerging in nursing practice, they offer significant potential for promoting comprehensive care, alleviating pain, and improving the quality of life for cancer patients. The study reinforces the need to integrate these practices into oncological care, emphasizing their value in humanizing treatment and preserving the dignity of patients at all stages of the disease.